A Wealth-Based Explanation for Earnings Conservatism - Lubberink, Martien; Huijgen, Carel (Review of Finance, 2001)
Abstract This study extends research on earnings conservatism – the degree to which the accounting system recognizes bad news regarding future cash flows in a more timely manner than good news – by arguing that heterogeneous executives' risk attitudes will influence the degree of conservatism. Prior research has demonstrated that differences in earnings conservatism are mainly the result of differences in institutional factors (Basu (1997) and Ball et al. (2000a)). We hypothesize that more risk-averse managers, who demand a risk premium that offsets the effects of the variance in their compensation, will report more conservative earnings. Earnings conservatism will temper expectations among stakeholders about the future cash flows to be distributed thereby diminishing the likelihood of disappointing outcomes and potential litigation or threats for executives of being fired. The more risk-averse manager would be more inclined to reduce such conflicts, since they will have a destabilizing effect on his future compensation. The empirical results for a sample of Dutch companies over the period of 1983 to 1995 confirm our hypothesis: more risk-averse managers report earnings more conservatively than do less risk-averse managers. JEL classification: G14, G38, M41.